ANALYSIS OF IMPLEMENTATION OF VIRTUAL MONEY AS AN EXCHANGE TO MEET NEEDS IN THE CLASS I ROUTINE, DEPOK - Ejo Imandeka; Agung Agung (Polteknik Ilmu Pemasyarakatan, 2020)
This study aims to analyze the form of application of virtual money as a medium of exchange in meeting the needs of the Class I detention center in Depok as an effort to optimize the duties and functions of detention centers in the service, maintenance and security of prisoners. As well as knowing what obstacles are experienced and are expected to find solutions. This research uses a qualitative research approach. Based on the results of research conducted by researchers, the application of virtual money as a medium of exchange has been implemented since August 2019, virtual money has been used by all prisoners and prisoners, one virtual accounts are used by one person and no one is the same, the media for using virtual money is the e-pass card and the corresponding fingerprint, and there are minimum and maximum limits on the amount of balances that can be stored in one virtual account. To optimize the application of virtual money as a medium of exchange, all parties must integrate each other in its application, coordinate with the parties responsible for maintaining facilities and operations, and be committed to improving services for meeting needs.